Integrating the ecosystem-based approach into municipal climate adaptation strategies: The case of Germany. (1st January 2018) - Zölch, Teresa; Wamsler, Christine; Pauleit, Stephan
Abstract: Climate change impacts are a key challenge for sustainable urban development. To address this challenge, ecosystem-based adaptation (EbA), i.e., the use of ecosystem services and biodiversity to help people adapt to climate change, is increasingly being considered as an alternative or complement to traditional, engineering-based approaches (increasingly also known as nature-based solutions). However, little research on ecosystem-based adaptation has been carried out in urban areas, and empirical evidence of its effectiveness and uptake in strategic adaptation planning is particularly lacking. Against this background, this study investigates the implementation of urban EbA in strategic adaptation planning. Based on a comparative analysis of all German municipalities with more than 100, 000 inhabitants, it examines the integration of EbA into municipal adaptation strategies. The results show that there is, so far, no comprehensive uptake of the EbA concept. While current strategies differ significantly in their type, structure, scope, maturity and content, overall the EbA concept remains implicit. 76% of the assessed strategies include some kind of ecosystem-based adaptation measures, which focus on enhancing the conservation, restoration, creation or sustainable management of ecosystems, and 25% of all strategies highlight the multiple benefits of these measures. However, comprehensive approaches are missing. We conclude that better policy support and comprehensive mainstreaming of EbA (e.g., through more distributed urban governance, science-policy integration, combined top-down policies and bottom-up activities) is urgently needed to foster sustainable urban development. Highlights: Progress/weaknesses in integrating ecosystem-based adaptation are investigated. The concept of ecosystem-based adaptation is not directly recognised. Ecosystem-based adaptation is seen as complementary to conventional adaptation measures. Making the concept a key component of policy would foster integration.